AMBIVALENCE OF PSYCHOLOGICAL FEATURES OF UKRAINIAN PEOPLE - Глотов, Б. Б. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Іn the article the comparative analysis of psychological features of the Ukrainian people in the East-West direction is made.